Penyajian Dan Pengungkapan Realisasi Anggaran Belanja Selama Masa Pandemi Covid-19 pada Kantor Pelayanan Pajak Pratama Bantaeng - Ika Sartika; Puji Wibowo (Universitas Prof.Hazairin,SH Bengkulu, 2021)
Covid-19 pandemic has caused the central government to issue new regulations for refocusing and reallocating the budget as a step in handling the impact of the pandemic in the government sector. Therefore, this study aims to review how Bantaeng Tax Office in responding new regulations and measure the quality of presentation and disclosure regarding the budget during the Covid-19 pandemic in financial statements. This study used primary data in the form of Unaudited financial statements in 2020 and Audited financial statements in 2019 as a comparison. The method used was content analysis resulting in quantitative and qualitative data. Based on the results of the study, KPP Pratama Bantaeng has been responsive in following up on the new regulations by revising the budget in the form of reallocation according to the priority of the work plan. Information regarding budget quantitatively has been presented 100% and completely. However, narrative details regarding the revision of the budget during 2020 and information regarding the Covid-19 budget account have not been disclosed. Thus, qualitatively it can be concluded that the disclosure is incomplete. In the future, important information, especially things that occur due to extraordinary phenomena such as Covid-19, is expected to be given a more detailed explanation in the financial statements.